2002
DOI: 10.1034/j.1600-6143.2002.20610.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sirolimus on Lipids in Renal Allograft Recipients: An Analysis Using the Framingham Risk Model

Abstract: This report describes the effects of sirolimus on plasma lipids, and uses the Framingham risk model to assess the clinical importance of these effects. Lipid data from two large controlled studies of 1295 renal transplant patients were analyzed retrospectively. Sirolimus 2 mg/day and 5 mg/day were compared with placebo or azathioprine, and administered concomitantly with steroids and cyclosporine over 12 months. Hypercholesterolemia and hypertriglyceridemia occurred in all treatment groups and were maximal at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
44
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 40 publications
9
44
0
Order By: Relevance
“…The hyperlipidemic effect of sirolimus is observed in the absence (50) and in the presence of ciclosporin (48,49). In addition, data from the clinical studies indicate that the hyperlipidemic effect of sirolimus is dose-dependent (41,49).…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 83%
See 4 more Smart Citations
“…The hyperlipidemic effect of sirolimus is observed in the absence (50) and in the presence of ciclosporin (48,49). In addition, data from the clinical studies indicate that the hyperlipidemic effect of sirolimus is dose-dependent (41,49).…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 83%
“…It has also been reported that treatment with sirolimus is associated with a dramatic increase in plasma triglycerides ranging from 65 to 100% (41,42,43,44,45,47). Patients receiving sirolimus 2 or 5 mg/day have been shown to have plasma triglycerides respectively 59 or 103 mg/dl greater than that of controls (41). In a multivariate analysis, sirolimus treatment was an independent factor associated with hypertriglyceridemia (43).…”
Section: Effects Of Mtor Inhibitors On Lipids "mentioning
confidence: 98%
See 3 more Smart Citations